Curadoria educativa: diálogo entre a crítica de processo e a crítica literária - Coelho, Flávia de Paiva (2025)
This project aims to study and reflect on the bias of an educational curatorship of exhibitions: PORTOS - Processes Orientados via Território e Ocupações Santistas, which was on view from June 17 to November 20, 2021 at Sesc Santos-SP and Ana Mendieta: Silhueta em Fogo | terra abrecaminhos, which was on view from September 19, 2023 to January 21, 2024 at S Sesc Pompeia in São Paulo. To this end, the following questions are highlighted: How does educational curation collaborate in the aesthetic and propositional construction for different audiences? To what extent does the creative process remain open when the exhibition interacts with the public? Taking as hypotheses the concepts made available by the exhibition in dialogue with the narrative proposal; educational curating as a mediation between the exhibition and the public, we seek to test the research problem. The study will be based mainly on the books of Cecilia Almeida Salles and her theoretical references, and Walter Benjamin, thinking from the point of view of process criticism and literary criticism. The methodology consists of a hypothetical-deductive approach, aimed at analyzing the corpus, based on documents, records, publications, reflecting the pertinence that involves the related fields of study and the collaborative process that has taken place since the conception